PEMBELAJARAN HARMONI LANJUTAN BERBASIS SECONDARY DOMINANT CHORD DAN MODAL INTERCHANGE PADA MATA KULIAH TEORI MUSIK LANJUTAN - Ricky Nelson; Trianus Homklom (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Secondary dominant chords and modal interchange are important parts of advanced harmony that play a role in developing students' musical analysis, arrangement, composition, and creativity skills. This study aims to describe the implementation of secondary dominant chord and modal interchange in the learning of Advanced Music Theory and identify the factors that influence its application. The research uses a qualitative approach with a case study method. Data was obtained through observation, interviews, and documentation of the learning process and students' musical assignments. Data analysis was carried out using the Miles, Huberman, and Saldaña models through data reduction, data presentation, and conclusion drawn. The results showed that students were able to implement secondary dominant chords through the use of temporary dominant chords to strengthen harmonic functions, while modal interchange was applied through the use of borrowed chords to enrich harmonic colors and musical expressions. The implementation of the two concepts is influenced by theoretical understanding, musical experience, exercise intensity, and learning strategies that integrate theory and practice. This study concludes that advanced harmony learning that is applicative can improve students' harmonic competence and musical creativity.